Accessing psychological therapies following self-harm: qualitative survey of patient experiences and views on improving practice. Issue 3 (11th May 2023) - Quinlivan, Leah; Gorman, Louise; Monaghan, Elizabeth; Asmal, Sadika; Webb, Roger T.; Kapur, Nav
Abstract : Background: Psychological therapies following an episode of self-harm should happen quickly to ensure patients receive the care they need and to reduce the likelihood of repetition. Aims: We sought to explore patients' subjective experience of accessing psychological therapies following self-harm and their views on improving practice. Method: Between March and November 2019, we recruited 128 patients and 23 carers aged 18 years or over from 16 English mental health trusts, from community organisations and via social media. Thematic analyses were used to interpret the data. Results: Participants reported long waiting times, multiple failed promises and rejection when trying to access psychological therapies following self-harm. Poor communication and information provision contributed to uncertainty, worsening mental health and further self-harm. Other barriers included: lack of tailored interventions, stigmatising responses, use of exclusionary thresholds to access services, and punitive approaches to treating these patients. Participant recommendations to improve access to psychological therapies included: (a) the importance of compassionate and informed staff; (b) having timely access to aftercare from well-funded and well-resourced teams; (c) continuity of care, improved communication, and support during waiting times and while navigating the referral process; (d) greater information on the availability and benefits of psychological therapies; and (e) greater choice and flexibility over interventions. Conclusion: Our findings identify long waiting times and inadequate service provision as barriers to high-quality and safe aftercare for patients who have self-harmed. Consistent with clinical guidelines, all patients should receive prompt aftercare and access to tailored psychological treatments following a self-harm episode.